Advanced Microfluidic‐Based Wearable Electrochemical Sensors for Continuous Biochemical Monitoring - Sehyun Park; Seongyeop Kim; Soojin Lee; Vladimir V. Tsukruk; SeungHyun Park; Hyo‐Ryoung Lim (Advanced Electronic Materials)
Abstract Microfluidic‐based wearable electrochemical sensors represent a transformative approach to non‐invasive, real‐time health monitoring through continuous biochemical analysis of body fluids such as sweat, saliva, and interstitial fluid. These systems offer significant potential for personalized healthcare and disease management by enabling real‐time detection of key biomarkers. However, challenges remain in optimizing microfluidic channel design, ensuring consistent biofluid collection, balancing high‐resolution fabrication with scalability, integrating flexible biocompatible materials, and establishing standardized validation protocols. This review explores advancements in microfluidic design, fabrication techniques, and integrated electrochemical sensors that have improved sensitivity, selectivity, and durability. Conventional photolithography, 3D printing, and laser‐based fabrication methods are compared, highlighting their mechanisms, advantages, and trade‐offs in microfluidic channel production. The application section summarizes strategies to overcome variability in biofluid composition, sensor drift, and user adaptability through innovative solutions such as hybrid material integration, self‐powered systems, and AI‐assisted data analysis. By analyzing recent breakthroughs, this paper outlines critical pathways for expanding wearable sensor technologies and achieving seamless operation in diverse real‐world settings, paving the way for a new era of digital health.